Hubungan Antara Body Image dengan Self Confidence Pada Remaja Putri di SMA Negeri 1 Wonosegoro - Bahri, Ahmad Syamsul; Anggiani, Esmita; Sutanta; Sudono, Bambang (Jurnal Indonesia Sehat, 2024)
Background: Body image is an individual's attitude towards body shape, body appearance, function and potential size of the body consciously and unconsciously. During adolescence, the perception of body image becomes stronger, especially in young women, a time when a person is going through a period of physical change and psychological development, which can make teenagers pay attention to their body shape and keep themselves busy to satisfy their appearance. The assessment among young women is that current body standards, which prioritize physical appearance with a proportional body shape, make today's young women less confident, young women always judge themselves through the eyes of other people, namely their social friends. Objective: Identifying the relationship between body image and self-confidence in young women at SMA Negeri 1 Wonosegoro. Method: This research uses quantitative methods with a cross sectional design. The sampling technique uses stratified random sampling, and data analysis uses Spearman's Rank correlation. Results: The results of data analysis from Spearman's rank were obtained???? value = 0.008 < ? = 0.05 which means the null hypothesis is rejected and the alternative hypothesis is accepted. So it can be concluded that there is a relationship between body image and self-confidence in young women at SMA Negeri 1 Wonosegoro. Conclusion: There is a relationship between body image and self-confidence in young women at SMA Negeri 1 Wonosegoro. With the direction of the relationship, the more positive a person's body image, the higher the level of self-confidence. Conversely, the more negative a person's body image, the lower their level of self-confidence.